2020
DOI: 10.1111/sms.13662
|View full text |Cite
|
Sign up to set email alerts
|

Gastrocnemius Medialis and Vastus Lateralis in vivo muscle‐tendon behavior during running at increasing speeds

Abstract: This study combines in vivo ultrasound measurements of the Vastus Lateralis (VL) and Gastrocnemius Medialis (GM) muscles with electromyographic, kinematic, and kinetic measurements during treadmill running at different speeds (10, 13, and 16 km/h) to better understand the role of muscle and tendon behavior in two functionally different muscle‐tendon units. In addition, the force‐length and force‐velocity relationships of VL and GM were experimentally assessed by combining dynamometry and EMG data with ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 46 publications
4
60
0
Order By: Relevance
“…Based on these theoretical considerations, if the whole muscle-tendon unit length changes could be attributed to the tendon only, the muscle fibres would operate under isometric conditions, reducing the fascicle length changes (and, therefore, the mechanical work done by the muscles) and the level of muscle activation required for a given force (Fletcher and MacInthos 2017). These theoretical notions were supported by recent studies of Bohm et al (2019) and Monte et al (2020), which revealed that the plantar flexor muscles operated quasi-isometrically at a high-force potential during running at different speeds. Furthermore, Bohm and co-workers found a negative significant correlation between the force-length-velocity potential of the soleus muscle and the energy cost of running at 10 km h −1 , suggesting that the higher the force potential the lower the energy expended.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Based on these theoretical considerations, if the whole muscle-tendon unit length changes could be attributed to the tendon only, the muscle fibres would operate under isometric conditions, reducing the fascicle length changes (and, therefore, the mechanical work done by the muscles) and the level of muscle activation required for a given force (Fletcher and MacInthos 2017). These theoretical notions were supported by recent studies of Bohm et al (2019) and Monte et al (2020), which revealed that the plantar flexor muscles operated quasi-isometrically at a high-force potential during running at different speeds. Furthermore, Bohm and co-workers found a negative significant correlation between the force-length-velocity potential of the soleus muscle and the energy cost of running at 10 km h −1 , suggesting that the higher the force potential the lower the energy expended.…”
Section: Introductionmentioning
confidence: 61%
“…2) suggests that the elastic energy provided by the Achilles tendon recoil during the propulsive phase would affect the total mechanical work provided by the body. Indeed, as showed by Monte et al (2020) with faster running speed, the GM muscle fascicle operating range shifts towards smaller lengths (on the ascending limb of the F-L relationship) yet operating quasi-isometrically and at a high force potential (> 80% of the maximum isometric force) and this behaviour allows the muscle fascicles to reduce the Fig. 2 Correlations between (positive) tendon work and total mechanical work (at the whole-body level), net energy cost of running and "apparent" efficiency at the three investigated speeds (blue dots: 10 km h −1 , red squares: 13 km h −1 , green triangles: 16 km h −1 ).…”
Section: Muscle and Tendon Contributionmentioning
confidence: 83%
See 3 more Smart Citations